Les territoires fragiles dans la région alpine : une proposition de lecture entre innovation et marginalité - Federica Corrado (Revue de Géographie Alpine)
The paper proposes a reading and description of fragile Alpine areas that overturns the conventional standpoint, according to which marginality is often synonymous with handicap. The paper starts form a different point of view, able to recognize specific local potentialities that can still be activated with a specific creative effort. The reading regards fragile Alpine areas in the Provinces of Turin and Cuneo and is based on an empirical analysis of the actions underlying current micro-territorial innovative development trends.